Dog Man : Unleashed - Pilkey, Dav, 1966-; Beard, George (Fictitious character); Hutchins, Harold (Fictitious character) (New York, NY : Graphix, an imprint of Scholastic, 2021)
"Dog Man . . . is still learning a few tricks of the trade. Petey the cat is out of the bag, and his criminal curiosity is taking the city by storm. Something fishy is going on! Can Dog Man unleash justice on this ruffian in time to save the city, or will Petey get away with the purr-fect crime?"--Amazon.com.
2.7
3-6.
3-6
Keywords: Dogs -- Comic books, strips, etc -- Juvenile fiction; Heroes -- Comic books, strips, etc -- Juvenile fiction; Humorous stories; Police -- Comic books, strips, etc -- Juvenile fiction; Cartoons and comics; Dogs -- Fiction; Heroes -- Fiction; Humorous stories; Police -- Fiction; Dogs -- Comic books, strips, etc -- Fiction; Heroes and heroines -- Comic books, strips, etc -- Fiction; Humorous graphic novels; Police -- Comic books, strips, etc -- Fiction; Funny animal comics; Graphic novels; Humorous comics